Development of Discussion Learning Model and Personal Investigation in Classroom Sociology Learning XI IPS SMA Muhammadiyah Enrekang - Suparman, Suparman; Darwis, Tri Wijaya; Samsul, Putriyani (Journal of Islam and Science, 2020)
The learning model used by teachers does not vary, resulting in the activeness and independence of students in learning is reduced. Therefore, a new learning model needs to be developed that stimulate the activeness and independence of students, namely the discussion learning model and personal investigation. This research used a Research and Development (R&D) approach. Researchers were focused on developing discussion learning models and personal investigations to be able developing a new learning model that can be applied in learning with clear steps according to scientific rules. The results of research were as follows: (1) students were more active in learning, (2) students no longer rely on friends when there are assignments or discussions, (3) problems that occur in learning can be analyzed by students easily, (4) Models could help foster a sense of responsibility in each student, especially responsibilities as a group member, (5) the learning process in the class was more enjoyable. Based on the analysis of research results and discussions, it can be concluded that the development of discussion learning models and personal investigations that have been implemented in sociology learning has a positive impact both for students and teachers. Students were more active in learning, and students were more independent and better identify social problems. The discussion learning model and personal investigation are appropriately applied in sociology learning in the classroom. Based on the results of the research, it was suggested that: (1) teachers should use different learning models in the learning process so that students are more active in the following learning, (2) This new learning model can be used as a reference for teachers in doing classroom learning, and (3) Discussion learning models and investigative personals can be applied by teachers in sociology learning.